Albuíno Cunha de Azeredo: trajetória educacional, empresarial e política de um engenheiro negro - Nascimento, Joyce Mazzoco do (2023)
This is an ethnography with the objective of analyzing the life trajectory of the character Albuíno Cunha de Azeredo, the first and only, until the year 2023, Black Governor of the State of Espírito Santo. Faced with this fact, we sought to analyze and describe the character's schooling process, the social, economic and cultural situation of his family in the course of his school/academic trajectory. Thus, this is a qualitative research with analysis of data from bibliographic sources, journalistic articles, memories and narratives of family members collected through interviews about Albuíno's trajectory. In addition, Bourdieu's (1989) life trajectory and Bertaux's (2010) life narrative methodologies are used. Through this research, reflections were carried out on the life trajectory of Albuíno Azeredo that unfolded in fields of analysis in Education, Business and Politics, based on the concept of memory articulated by Michel Pollak (1989) and Beatriz do Nascimento (1982, 2006 and 2018). In this way, it was understood that the collective memory is in constant dispute through the memory framing mechanism and the choice to analyze the life trajectory of Albuíno Azeredo is an anti-racist practice in bringing to the memory what this great character represents.